Mechanical properties of wire arc additive manufactured carbon steel cylindrical component made by gas metal arc welding process - Nagasai Bellamkonda Prasanna (De Gruyter, 2021)
Wire arc additive manufacturing (WAAM), a welding-based additive manufacturing (AM) method, is a hot topic of research since it allows for the cost-effective fabrication of large-scale metal components at relatively high deposition rates. In the present study, the cylindrical component of low carbon steel (ER70S-6) was built by WAAM technique, using a GMAW torch that was translated by an automated three-axis motion system using a rotation table. The mechanical properties of the component were evaluated by extracting tensile, impact toughness and hardness specimens from the two regions of the building up (vertical) direction. It is found that the tensile properties of the built material exhibited anisotropic characteristics. The yield strength and ultimate tensile strength varied from 333 to 350 MPa and from 429 to 446 MPa, respectively, (less than 5 % variation).